MET kinase inhibitor reverses resistance to entrectinib induced by hepatocyte growth factor in tumors with NTRK1 or ROS1 rearrangements - Yohei Takumi; Sachiko Arai; Chiaki Suzuki; Koji Fukuda; Akihiro Nishiyama; Shinji Takeuchi; Hiroki Sato; Kunio Matsumoto; Kenji Sugio; Seiji Yano (Cancer Medicine, 2023)
Abstract Background Entrectinib is an effective drug for treating solid tumors with NTRK gene rearrangement and non‐small cell lung cancer (NSCLC) with ROS1 gene rearrangement. However, its efficacy is limited by tolerance and acquired resistance, the mechanisms of which are not fully understood. The growth factors produced by the tumor microenvironment, including hepatocyte growth factor (HGF) produced by tumor‐associated fibroblasts, critically affect the sensitivity to targeted drugs. Methods We investigated whether growth factors that can be produced by the microenvironment affect sensitivity of NTRK1‐rearranged colon cancer KM12SM cells and ROS1‐rearranged NSCLC HCC78 cells to entrectinib both in vitro and in vivo. Results Among the growth factors assessed, HGF most potently induced entrectinib resistance in KM12SM and HCC78 cells by activating its receptor MET. HGF‐induced entrectinib resistance was reversed by the active‐HGF‐specific macrocyclic peptide HiP‐8 and the MET kinase inhibitor capmatinib in vitro. In addition, HGF‐producing fibroblasts promoted entrectinib resistance in vitro (culture model) and in vivo (subcutaneous tumor model). The use of capmatinib circumvented entrectinib resistance in a subcutaneous tumor model inoculated with KM12SM and HGF‐producing fibroblasts. Conclusion Our findings suggest that growth factors in the tumor microenvironment, such as HGF, may induce resistance to entrectinib in tumors with NTRK1 or ROS1 rearrangements. Our results further suggest that optimally co‐administering inhibitors of resistance‐inducing growth factors may maximize the therapeutic efficacy of entrectinib.